МИКОЛА МІХНОВСЬКИЙ: МІЖ ДВОМА РЕВОЛЮЦІЯМИ (1907–1917 рр.) (Zaporizhzhia Historical Review, 2021)
The article is a fragment of the political biography of a well-known Ukrainian statesman and publicist – Mykola Mikchnovskiy. The evolution of his social and political outlook from socialism to conservatism is emphasized.